+0  
 
0
49
1
avatar

Solve \( \log_2{(x-5)} = \log_4{(x-2)} + 1\)

 Jul 30, 2020
 #1
avatar+21953 
+1

Solve:     log2(x - 5)  =  log4(x - 2) + 1

 

First, using the change-of-base formula, I'm going to write log4(x - 2) as a base two log:

                 log4(x - 2)  =  log2(x - 2) / log2(4)  =  log2(x - 2) / 2  =  ½·log2(x - 2)

 

 log2(x - 5)  =  log4(x - 2) + 1     --->      log2(x - 5)  =  ½·log2(x - 2) + 1

                                       log2(x - 5) - ½·log2(x - 2)  =  1

                                         log2(x - 5) - log2(x - 2)½  =  1

                                           log2[ (x - 5) / (x - 2)½  ]  =  1

                                                       (x - 5) / (x - 2)½  =  2

                                                                      (x - 5)  =  2·(x - 2)½ 

squaring both sides:                           x2 - 10x + 25  =  4(x - 2)

                                                           x2 - 10x + 25  =  4x - 8

                                                           x2 - 14x + 33  =  0

                                                           (x - 11)(x - 3)  =  0

                                                     either     x = 11    or     x = 3

 

If you check the possible answers, you'll see that 11 works but 3 doesn't.

 Jul 30, 2020

27 Online Users

avatar